Profesionalisme Guru Pendidikan Anak Usia Dini dalam Proses Belajar Mengajar - Jefrianus Da Silva; Refni Fajar Wati Zega; Lily Peggy Kawatu; Berkati Bu’ulolo (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Professional teachers are very important in early childhood education. However, PAUD teachers often do not prioritize teaching skills, which becomes a problem. This research discusses the professionalism of PAUD teachers in the learning process using descriptive qualitative methods to find solutions. Teachers must be teachers and motivators who are responsible for shaping children's personalities and have mature skills and preparation before teaching. In conclusion, professional teachers are those who have expertise and skills in educating early childhood children and creating a fun and interesting learning atmosphere.